The effect of soil water content, pH and temperature on the N supplying capacity of vineyard soils in the Western Cape - Raath, Pieter J.(Pieter Johannes) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1995.